The Student Loan Debt Crisis in the United States and the Long-Term Economic Impact - Alexander, F. King (International Higher Education, 2024)
The student loan indebtedness issue has become one of the most significant issues in higher education in the United States. This issue impacts nearly 45 million Americans and has long-term economic consequences that are just beginning to be felt throughout the country’s economy. This article addresses the evolution of this national problem and discusses the economic ramifications of the student loan debt crisis.